2007
DOI: 10.1002/hyp.6548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moving storms on attainment of equilibrium discharge

Abstract: Although rainfall is assumed spatially uniform in conventional hydrological modelling for rainfall-runoff simulations, moving storms have been shown to have substantial influence on flow hydrographs. In this study, criteria for attainment of the equilibrium discharge from watersheds subjected to moving storms were examined. Non-linear numerical kinematic-wave models were developed to simulate runoff from an overland plane and from a V-shaped catchment. Dimensional analysis was applied to obtain the independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Even if L s / L cl < 1, the PDR can reach the equilibrium states as shown in Figures 6, 7, and 8a depending on t c / t h . This result is consistent with that of Lee and Huang [2007] who found that runoff can attain equilibrium discharge for storms moving downstream even though the storm length is smaller than the catchment and the duration is less than the time to equilibrium for stationary storms.…”
Section: Resultssupporting
confidence: 92%
“…Even if L s / L cl < 1, the PDR can reach the equilibrium states as shown in Figures 6, 7, and 8a depending on t c / t h . This result is consistent with that of Lee and Huang [2007] who found that runoff can attain equilibrium discharge for storms moving downstream even though the storm length is smaller than the catchment and the duration is less than the time to equilibrium for stationary storms.…”
Section: Resultssupporting
confidence: 92%
“…Instead of applying the model to a natural watershed, a conceptual overland plane model was adopted to alleviate the influence of complex landform on runoff hydrograph generation. The overland plane model, which had been employed by various researchers for a runoff sensitivity experiment [19], hydrological model development and verification [8,21,29,30], a moving storm analysis [13,28] and rainfall intensity-duration curve formulation [4], had obtained constructive results. In this study, surface of the overland plane was designated to spatially systematic and randomly distributed roughness scenarios for rainfall-runoff simulations (as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In order to illustrate how a moving rainstorm with variable spatial extent interacts with the basin characteristics, giving rise to partial resonance effects, we apply the analytical framework described above to the simple case of the open-book idealized catchment (Lee and Huang, 2007). In this case we can write the g function in an analytical form.…”
Section: Illustrative Example: Open-book Idealized Catchmentmentioning
confidence: 99%
“…de Lima and Singh, 2002;Foroud et al, 1984;Lee and Huang, 2007;Ngirane-Katashaya and Wheater, 1985;Niemczynowicz, 1984a,b;Ogden et al, 1995;Stephenson, 1984;Surkan, 1974;Watts and Calver, 1991) or analytical solutions derived under the kinematic-wave approximation (Singh, 1998(Singh, , 2005. For a comprehensive review see Singh (1997) and Lee and Huang (2007). Recently Viglione et al (2010b) following an earlier work by Woods and Sivapalan (1999) built a general framework to quantify the contribution of spatio-temporal variability of rainfall intensity, runoff coefficient, hillslope and channel velocities, and storm movement to the resulting flood peaks.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation